Accidental Immigrants and the Search for Home : Women, Cultural Identity, and Community - Kelley, Carol E., 1959- (Book collections on Project MUSE., 2013)
The effect of immigration on individual lives is not short lived. Those who stay in an adopted country permanently go through a continual process of adjustment and learning both about their new country - and about themselves. The four women profiled in this book challenge immigrant stereotypes as their lives are transformed by moving to new countries for reasons of marriage, education, or career - not economics or politics. The intimate stories of these "accidental" immigrants broaden conventional notions of home.